2017
DOI: 10.1007/s13197-016-2467-6
|View full text |Cite
|
Sign up to set email alerts
|

Fractionation of unreduced gluten proteins on SEC and their relationship with cookie quality characteristics

Abstract: The size distribution assessment of unreduced wheat gluten proteins of commercial Indian wheat varieties was examined using Size-Exclusion Fast Protein Liquid Chromatography. Elution profiles were fractionated into five peaks, with the molecular weights of eluting peaks as 130-30, 55-20, 28-10 and <10 kDa (IV and V), respectively. Peak I (glutenins) and II (gliadins) exhibited contrary results with AWRC (r = 0.928** and r = -0.831**), R/E ratio (r = 0.745** and r = -0.869**), gluten index (r = 0.959** and r = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…In fact, Chaudhary et al . () reported that the wheat varieties with proteins with lower molecular weight were better for cookie making. Furthermore, the use of proteases can also improve the quality of cookies (Kara et al ., ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, Chaudhary et al . () reported that the wheat varieties with proteins with lower molecular weight were better for cookie making. Furthermore, the use of proteases can also improve the quality of cookies (Kara et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Goel et al (1999) and Ribotta et al (2012) found that incorporation of enzymatically hydrolysed proteins decreased the viscosity and rheological profiles of starchy pastes. In fact, Chaudhary et al (2017) reported that the wheat varieties with proteins with lower molecular weight were better for cookie making. Furthermore, the use of proteases can also improve the quality of cookies (Kara et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…SDS-PAGE was carried out for 40% and 80% acetone precipitated fractions and SEC eluted protein fractions by using electrophoretic assembly of M/S Genetix Scientific (India) as described previously by Chaudhary et al (2016aChaudhary et al ( , 2017. Electrophoresis was performed on 12% separating gel and 4% stacking gel.…”
Section: Sds Polyacrylamide Gel Electrophoresismentioning
confidence: 99%
“…The gluten proteins have been strongly acknowledged to personate a prominent act in defining the functional properties and processability of wheat flour (N. Chaudhary et al, 2016aChaudhary et al, , 2016cChaudhary et al, , 2017. The protein functionality is linked to its conformational state, which is predominantly restrained by the processing parameters (Chaudhary et al, 2022;Dewan et al, 2022).…”
Section: Introductionmentioning
confidence: 99%